2019
DOI: 10.1002/anie.201813559
|View full text |Cite
|
Sign up to set email alerts
|

A Water‐Soluble Perylene Bisimide Cyclophane as a Molecular Probe for the Recognition of Aromatic Alkaloids

Abstract: Herein, we report a water‐soluble macrocyclic host based on perylene bisimide (PBI) chromophores that recognizes natural aromatic alkaloids in aqueous media by intercalating them into its hydrophobic cavity. The host–guest binding properties of our newly designed receptor with several alkaloids were studied by UV/Vis and fluorescence titration experiments as the optical properties of the chromophoric host change significantly upon complexation of guests. Structural information on the host–guest complexes was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 53 publications
3
28
0
Order By: Relevance
“…As a consequence of their large π‐surfaces, PBIs bridged with para ‐xylylene spacer units proved to be excellent hosts with high binding affinities for polycyclic aromatic hydrocarbons[ 14 , 15 ] and even some alkaloids. [16] Furthermore, similar to previously described examples,[ 8 , 9 ] chirality transfer from chiral guest molecules to achiral PBI cyclophanes could be observed by CD spectroscopy. [17] Inspired by this work, we have now designed the first example of an inherently chiral PBI cyclophane host.…”
supporting
confidence: 79%
“…As a consequence of their large π‐surfaces, PBIs bridged with para ‐xylylene spacer units proved to be excellent hosts with high binding affinities for polycyclic aromatic hydrocarbons[ 14 , 15 ] and even some alkaloids. [16] Furthermore, similar to previously described examples,[ 8 , 9 ] chirality transfer from chiral guest molecules to achiral PBI cyclophanes could be observed by CD spectroscopy. [17] Inspired by this work, we have now designed the first example of an inherently chiral PBI cyclophane host.…”
supporting
confidence: 79%
“…As a consequence of their large p-surfaces, PBIs bridged with para-xylylene spacer units proved to be excellent hosts with high binding affinities for polycyclic aromatic hydrocarbons [14,15] and even some alkaloids. [16] Furthermore, similar to previously described examples, [8,9] chirality transfer from chiral guest molecules to achiral PBI cyclophanes could be observed by CD spectroscopy. [17] Inspired by this work, we have now designed the first example of an inherently chiral PBI cyclophane host.…”
supporting
confidence: 79%
“…In this study, strategically, the naphthyl moiety with an ortho ‐methoxy group (NM) and perylene bisimide (PBI) units were chosen as a donor and an acceptor, respectively, which are separated by an alkynyl linker, rendering a D‐A system, PBI‐2NM (Figure ). PBI was selected because of its advantages of low LUMO level, intense emission, and excellent photostability . 1 H NMR studies revealed that the oxygen atom in the ortho ‐methoxy group of the NM moiety and an aromatic hydrogen atom (H a , see Figure ) of the PBI core could form a weak but effective H‐bond (Ar−H⋅⋅⋅O, where Ar stands for an aromatic ring), allowing stabilization of a π‐conjugated configuration owing to blocking of the free rotation of the linker.…”
Section: Introductionmentioning
confidence: 99%